1996
DOI: 10.1016/s0304-3959(96)03188-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensory dysfunction in fibromyalgia patients with implications for pathogenic mechanisms

Abstract: This study, addressing etiologic and pathogenic aspects of fibromyalgia (FM), aimed at examining whether sensory abnormalities in FM patients are generalized or confined to areas with spontaneous pain. Ten female FM patients and 10 healthy, age-matched females participated. The patients were asked to rate the intensity of ongoing pain using a visual analogue scale (VAS) at the site of maximal pain, the homologous contralateral site and two homologous sites with no or minimal pain. Quantitative sensory testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
181
3
10

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(211 citation statements)
references
References 52 publications
17
181
3
10
Order By: Relevance
“…Although the small CI indicates robustness of the finding that the accuracy of detecting heart beats does not differ between FM patients and healthy controls, it is opposed to previous results showing increased pain sensitivity and amplified perception of painful and non-painful stimuli in FM patients (2,3,(7)(8)(9). The present finding, however, is in line with a number of studies, which failed to demonstrate prioritization of external innocuous stimuli in FM patients (4,41).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Although the small CI indicates robustness of the finding that the accuracy of detecting heart beats does not differ between FM patients and healthy controls, it is opposed to previous results showing increased pain sensitivity and amplified perception of painful and non-painful stimuli in FM patients (2,3,(7)(8)(9). The present finding, however, is in line with a number of studies, which failed to demonstrate prioritization of external innocuous stimuli in FM patients (4,41).…”
Section: Discussionsupporting
confidence: 50%
“…interoception, is scarce. So far, generalized hypervigilance has been supported by (a) self-report measures, on which FM patients typically show elevated scores for vigilance to pain (4)(5)(6) and (b) experimental measures showing decreased pain thresholds and tolerance levels for experimentally induced pain (2,7,8) innocuous (e.g. auditory) stimuli (3,9) and (c) perceptual amplification of nonaversive interoceptive stimulation (10) in FM patients.…”
Section: Introductionmentioning
confidence: 99%
“…The results are also not in line with those of Brown et al (2010), who suggested that there might be an interrelation between illusory tactile perceptions and the degree of pseudoneurological symptoms, nor with Katzer et al (2011) who suggested medically unexplained symptoms might be related to touch illusions, because both groups in the present study reported a comparable number of vicarious somatosensory experiences. Some previous studies have demonstrated that patients with FM have a hypersensitivity for mechanical, cold and heat pain perception (Kosek et al, 1996;Smith et al, 2008) and mixed results exist for non-painful sensations such as cold, warm and touch (Desmeules et al, 2003;Klauenberg et al, 2008). The results of the present study show that threshold intensities for vibrotactile stimuli, although individually determined, were not significantly different for both groups.…”
contrasting
confidence: 48%
“…There are research findings suggesting that fibromyalgia may be a neurological disorder characterized by ''central sensitization''. Abnormalities in pain processing [5,23], central pain modulation [25,28] and secondary hyperalgesia [2] have been reported. There are also reports of reduced thalamic blood flow [24,30], and elevated levels of nerve growth factor [15] and the neurotransmitter substance P [36,42] in the cerebrospinal fluid of fibromyalgia patients.…”
Section: Discussionmentioning
confidence: 99%